RI 5354 The Role Of Viscosity In Dense-Medium Coal Cleaning ? Introduction And Summary - M. R. Geer (The National Institute for Occupational Safety and Health (NIOSH), 1957)
The widespread adoption during the past decade of the dense-medium process for cleaning coal increases the need for technologic studies of the process. Such studies provide information that will insure maximum usefulness of this process in its present form and may well lead to substantial improvements in design and opera¬tion. The Bureau of Mines has published the results of cleaning trials on a wide variety of coals in two dense-medium pilot plants5/ and reported the recovery of coal from waste by dense-medium treatment.6./ The present report deals with the viscosity of magnetite dense medium, an important subject about which virtually nothing has been published. Specifically, the report concerns methods for measuring viscosity, the influence of various medium contaminants on viscosity, the effect of viscosity on cleaning results, and the influence of viscosity on consumption of medium. Cleaning trials on four coals of varied density composition in a pilot plant, using mediums of different viscosities, showed a steady reduction in cleaning efficiency with increasing viscosity in every instance. However, the behavior of each coal in a viscous medium was distinctly individual. With one, an increase of only 1 centipoise in viscosity caused a reduction in recovery efficiency of 7.7 percent, whereas the same increase in viscosity with another reduced recovery efficiency only 2.7 percent.